Impact of robotic-assisted versus video-assisted thoracoscopic surgery on efficacy and quality of life in patients with pulmonary opacities: a propensity score-matched analysis - Huang, Liuchun; Liang, Shengjing; He, Jing; Qin, Junqi; Wei, Jiaping; Huang, Jianwei; Peng, Shucong; Chen, Xianglan; Pan, Chunhui; Pen, Huifang; Wen, Yu; Zhou, Yifan; et al. (Frontiers in Oncology, 2025)
ObjectiveWith the increasing detection of pulmonary opacities through low-dose computed tomography (LDCT), minimally invasive surgical techniques have gained prominence. While debates persist regarding the comparative efficacy and postoperative quality of life (QOL) between robot-assisted thoracoscopic surgery (RATS) and video-assisted thoracoscopic surgery (VATS), this study aimed to compare the perioperative outcomes and postoperative QOL between RATS and VATS in patients with pulmonary opacities.MethodsA retrospective analysis was performed on patients who underwent pulmonary opacities resection at the Department of Thoracic Surgery, Guangxi Zhuang Autonomous Region People’s Hospital, between January 2021 and November 2024. Patient characteristics, perioperative clinical indicators, economic parameters, and QOL scores were analyzed.ResultsA total of 1,173 patients undergoing RATS and VATS was conducted, after propensity score matching, 277 pairs of patients entered into final analysis. Baseline characteristics were similar between groups. Compared with VATS, RATS had shorter operative time (145.35 ± 48.51 vs. 170.39 ± 71.49, p < 0.001), less intraoperative blood loss [20 (10, 20) mL vs. 30 (20, 100) mL, p < 0.001], shorter chest tube duration (3.82 ± 1.28 vs. 4.28 ± 2.63 days), less 48-hour postoperative drainage (217.73 ± 107.69 mL vs. 244.01 ± 120.48 mL, p = 0.007), shorter postoperative hospital stay (6.05 ± 1.54 vs. 7.14 ± 5.04, p = 0.001), and lower overall postoperative complication rate than the VATS group (9.39% vs. 15.52%, p = 0.029). But, total hospitalization costs were higher in the RATS group. Moreover, the Visual Analogue Scale (VAS) score on postoperative day 3 in the RATS group was significantly lower (p < 0.001). At 3 months postoperatively, the RATS group reported significantly less pain/discomfort (p = 0.015) in the QOL assessment.ConclusionRATS indicated shorter operative time, reduced postoperative complications, shorter hospital stay, less intraoperative blood loss and less compared to VATS in patients with pulmonary opacities. Although hospitalization costs were higher, RATS was associated with improved postoperative pain management and QOL regarding pain/discomfort.